Combined fibrolamellar carcinoma and cholangiocarcinoma exhibiting biphenotypic antigen expression: a case report. Issue 8 (27th July 2005) - Tanaka, K; Honna, T; Kitano, Y; Kuroda, T; Tanaka, K; Morikawa, N; Matsuda, H; Kawashima, N; Matsuoka, K; Miyauchi, J
Abstract : Fibrolamellar carcinoma (FLC), a variant of hepatocellular carcinoma (HCC), very rarely occurs in association with cholangiocarcinoma (CC). This report describes the first case of FLC coexisting with CC (FLC-CC) from Japan. Although the major part of the tumour located in the right lobe of the liver showed the typical features of FLC, CC was admixed with the FLC, not only in the primary hepatic tumour, but also in the lymph node metastases. Immunohistochemical analysis revealed that, although carcinoembryonic antigen (CEA), which can be detected with monoclonal antibodies in the cytoplasm and the cell surface of CC cells but not HCC cells, was expressed in only the CC cells in the primary tumour, it was expressed extensively in the cytoplasm of both CC and FLC cells in the metastatic and recurrent tumours. Furthermore, Hep Par 1, a hepatocyte specific antigen, was also expressed in both the FLC and CC cells. These findings suggest that, in this case, both FLC and CC were possibly derived from the same cancer stem cell with the capacity to differentiate into both hepatocytes and bile duct epithelium, and that both the cellular components, therefore, exhibited biphenotypic antigen expression.